ANALISIS GERAKAN DAKWAH KHALID BASALAMAH DI YOUTUBE - Mustafa Mustafa; Ridzki K Mangkarto (Ahsan: Jurnal Dakwah dan Komunikasi, 2022)
Da'wah on social media has been very much used, and its application, with the sole purpose of meeting the demands of the times and expanding the reach of Islamic proselytizing, one of the Youtube channels that actively produces proselytizing content is Khalid Basalamah Official. The purpose of this article is to analyze the content of the qualitative message of the proselytizing movement on Youtube social media, with the qualitative content analysis method initiated by Harold D. Lasswell in this study playing a role in the content of the communication that is expressed (visible or manifest) otherwise the implied communication content (latent) is not used in this study. Furthermore, virtual observation data collection techniques are used on the Khalid Basalamah Official Youtube channel. As a result, Youtube is one of the social media that was able to become a massive alternative proselytizing movement by Ustadz Khalid Basalamah